PENYULUHAN HUKUM DAN KESEHATAN DI KECAMATAN CARENANG KABUPATEN SERANG - Encep Saefullah; Mohammad Hifni; Popi Dayurni; Arifah Imanun; Nur Achmad Sahfudin; Rizki Dwi Prayoga; M Aburizal Rahmadani (Yayasan Education and Social Center, 2023)
The social phenomenon in Carenang District, Serang Regency reflects a serious challenge in the form of high levels of juvenile delinquency, particularly among school students, which include student brawls, drug abuse, and free sex. This phenomenon is caused by a lack of understanding of the law and a lack of awareness of the negative impact on health from the consumption of illegal drugs and free sex. In response to this, community service activities have been initiated with the aim of providing education to the community, especially school-age adolescents, through counseling on law and health. Through this approach, the implementation of service activities is able to increase the knowledge and understanding of young people and society in general regarding legal and health aspects. This effort is an important step in responding to social phenomena that impact the younger generation and society in general, helping to increase awareness and quality of life in Carenang District